Annual Research Review: Achieving universal health coverage for young children with autism spectrum disorder in low‐ and middle‐income countries: a review of reviews. (27th April 2021) - Divan, Gauri; Bhavnani, Supriya; Leadbitter, Kathy; Ellis, Ceri; Dasgupta, Jayashree; Abubakar, Amina; Elsabbagh, Mayada; Hamdani, Syed Usman; Servili, Chiara; Patel, Vikram; Green, Jonathan
Abstract : Background: Autism presents with similar prevalence and core impairments in diverse populations. We conducted a scoping review of reviews to determine key barriers and innovative strategies which can contribute to attaining universal health coverage (UHC), from early detection to effective interventions for autism in low‐ and middle‐income countries (LAMIC). Methods: A systematic literature search of review articles was conducted. Reviews relevant to the study research question were included if they incorporated papers from LAMIC and focused on children (<eight years old) with autism or their caregivers. The database search was supplemented with bibliographic search of included articles and key informant suggestions. Data were extracted and mapped onto a Theory of Change model toward achieving UHC for autism in LAMIC. Results: We identified 31 articles which reviewed data from over fifty countries across Africa, Latin America, Middle East, and Asia and addressed barriers across one or more of four inter‐related domains: (a) the social context and family experience for a child with autism; (b) barriers to detection and diagnosis; (c) access to appropriate evidence‐based intervention; and (d) social policy and legislation. Key barriers identified included: lack of appropriate tools for detection and diagnosis; low awareness and experienced stigma impacting demand for autism care; and the prevalence of specialist models for diagnosis and treatment which are not scalable in LAMIC. Conclusions: We present a Theory of Change model which describe the strategies and resources needed to realize UHC for children with autism in LAMIC. We highlight the importance of harnessing existing evidence to best effect, using task sharing and adapted intervention strategies, community participation, and technology innovation. Scaling up these innovations will require open access to appropriate detection and intervention tools, systematic approaches to building and sustaining skills in frontline providers to support detection and deliver interventions embedded within a stepped care architecture, and community awareness of child development milestones.